Integrating the Who, What, and Where of U.S. Retail Center Geographies. (7th February 2023) - Ballantyne, Patrick; Singleton, Alex; Dolega, Les; Macdonald, Jacob
Abstract : Retail is an important function at the core of urban areas, occupying a key role in determining their economic prosperity, desirability, and vibrancy. Efforts to understand the geographies of retail centers, the cores of retailing in urban areas, have a long academic tradition, often studied through either rich local case studies, or when geographically more expansive, are constrained by limited detail. New data in United States detailing the location and uses of retail creates a significant opportunity to develop a more complete and comprehensive overview of the national retail system, at a high spatial resolution. This research is rooted in a pragmatic effort to provide the first and most comprehensive model of U.S. retail center geographies, through development of an integrated, conceptual, and empirically grounded framework, using data from SafeGraph, to examine where they are located, what characteristics they have, and who uses them. The resulting geographies are of great interest, creating significant potential in the monitoring of the national retail system as it continues to evolve in response to wider structural challenges. Furthermore, by integrating these three geographies (where, what, and who), we establish a conceptual framework that yields substantive insights about the relationships between each of them, and argues that understandings of U.S. retail center geographies are more comprehensive and useful when considering the who, what, and where together.